Effects of complex strength training with elastic band program on repeated change of direction in young female handball players: Randomized control trial. Issue 6 (December 2022) - Hammami, Mehrez; Gaamouri, Nawel; Cherni, Yosser; Gaied, Sabri; Chelly, Mohamed Souhaiel; Hill, Lee; Nikolaidis, Pantelis Theodoros; Knechtle, Beat
This study examined the effect of 10-week complex strength training with elastic band program on fitness components in young female handball players. Thirty-eight handball players aged 15.8 ± 0.2 years were randomly assigned to an experimental group or control group. The experimental group performed complex strength training with elastic band twice a week over 10 weeks, which included 8 workshops of progressing set length (number of sets) and band resistance for each specific exercise. Sessions were lasted approximately 35 min. The control group maintained regular in-season training. Tests included handgrip; back extensor; medicine ball throw; 30 m sprint times; Modified Illinois change-of-direction (Illinois-MT); four jump tests (squat jump, countermovement jump, countermovement jump with arms and five jump test; static (stork test) and dynamic (Y balance test) balance; and repeated sprint T-test. The experimental group enhanced all strength performance (handgrip right ( p < 0.001), handgrip left ( p < 0.001), back extensor strength ( p < 0.001) and medicine ball throw ( p < 0.001) compared to the controls); sprint performance (5 m ( p <0.001), 10 m ( p < 0.001), 20 m ( p < 0.001), and 30 m ( p < 0.001)); the change of direction (Illinois-MT ( p < 0.001)); jump performance (squat jump ( p < 0.001), countermovement jump ( p < 0.001), countermovement jump with arms ( p < 0.001), and five jump test ( p < 0.01)); and the repeated sprint T-test scores ( p <0.001in all scores). In contrast, no significant difference in both static and dynamic balance performance between experimental group and control group. Ten weeks of complex strength training with elastic band improve fitness components measures in young female handball players then habitual training.